LEARNING TO DETECT LPI RADAR SIGNALS: A STUDY OF STRUCTURE IN FREQUENCY MODULATED NOISE WAVEFORM - Виплавін, Павло; Лукін, Костянтин (SWorldJournal, 2025)
This paper investigates the detectability of a structured noise radar waveform using a shallow convolutional neural network (CNN). The waveform under study is generated by frequency modulation of a constant-envelope carrier with low-bandwidth Gaussian noi